DYRK1A-related intellectual disability syndrome: a cohort of Portuguese patients - Raquel Gouveia-Silva; João Rodrigues-Alves; Juliette Dupont; Oana Moldovan; Patrícia Dias; Márcia Rodrigues; Ana Medeira; Ana B. Sousa (Publicaciones Permanyer, 2024)
Introduction: DYRK1A heterozygous pathogenic variants have been shown to cause a syndromic form of intellectual disability (ID) with impaired speech development, features of autism spectrum disorder (ASD), microcephaly, and a recognizable facial gestalt that evolves with age. Patients can also present with gait disturbance or hypertonia, epilepsy, brain imaging, ocular, and foot anomalies. Methods: This is a cross-sectional study. Clinical data on patients with DYRK1A pathogenic variants identified at the Clinical Genetics Department of Santa Maria Hospital, in Lisbon, were retrospectively collected from medical records using a detailed clinical questionnaire. Results: We describe eight unrelated patients, six females and two males, aged 4 to 24. Fetal growth restriction (FGR) was present in 5/8, and microcephaly in 7/8. ID, ranging from mild to severe, and language impairment or absent speech were documented in all patients. ASD and/or stereotypic behavior were reported in 6/8. Five patients presented visual anomalies, most commonly optic disc pallor (in 4). Three main facial features were consistently reported: deep-set eyes, thin upper lip, and micro/retrognathia. Foot and hand anomalies were frequent. Discussion/Conclusions: Our cohort illustrates the variable degree of severity of a syndromic form of ID, which includes mild cases. Microcephaly and a typical neurobehavioral phenotype are in accordance with the literature, as well as some common dysmorphisms. Interestingly, optic disc pallor seems to be a frequent finding, highlighting the need for ophthalmological surveillance. Our study adds evidence to the existence of a consistent clinical phenotype of DYRK1A-related ID, hopefully contributing to increased awareness and improving the recognition of this entity.